Optimizing acitretin use in patients with plaque psoriasis. Issue 2 (20th December 2016) - Chiricozzi, Andrea; Panduri, Salvatore; Dini, Valentina; Tonini, Annalisa; Gualtieri, Bruno; Romanelli, Marco
Abstract: Acitretin is one of the systemic agents used for the treatment of psoriasis. Because different acitretin dosages resulted therapeutically successful, there is no general agreement on the optimal dose regimen. To report acitretin efficacy and safety in a real‐life setting, wherein patient‐tailored dose regimen is usually prescribed, a retrospective analysis evaluating charts of all plaque‐type psoriasis patients treated with acitretin from the clinic database was performed. PASI score improvement, as well as PASI 50, 75, 90, and 100 responses were assessed throughout the observational period. Overall, 52% PASI score reduction and a satisfactory safety profile were detected. PASI 50, 75, 90, and 100 response was achieved by 53%, 48%, 28%, and 14%, respectively. Treatment consisted on a mean daily acitretin dose of 25.01 mg. The initial dose was increased (51.2% of cases) or decreased (48.8%) prescribing a mean daily dose of 29.8 mg and 20.02 mg, respectively. This study proposed a dose regimen customized on clinical response and patient's needs, to optimized acitretin benefit.